What makes a child happy? The link between family Income, social networks and subjective well-being in Vietnam - Nguyen, N (Young Lives, 2011)
Using cross-sectional data from the Young Lives survey for a cohort of 12-year-old children in Vietnam, we find that children from ethnic minority and poor households have lower subjective well-being, on average, than those from ethnic majority and non-poor households. Absolute income is positively correlated with subjective well-being but no longer is significant once relative income is controlled for. There is some evidence that income-happiness is an inverted U-shape relationship, which means that there are diminishing returns to income. In addition, other variables such as caregiver’s happiness, father’s education and nutrition status as well as some social network variables are significantly correlated with a child’s happiness.